Seed-Borne Infection Colletotrichum (Schw.) Andrus and Moore in Soybean Seeds and its Control - Srichuwong, Sombat (1992)
C. truncatum have been recognized as a soybean seed pathogen for over 40 years, causing pre-and post- emergence damping-off of seedlings and seedling blight. Although much is known of the effects of this pathogen on soybean seed quality and vigour, fundamental studies on the pathogen, its seed-borne nature, seed transmission and control are rather limited. Present studies are thus focused on their issues. Detection and isolation of this pathogen was carried out in order to understand the nature of the seed-borne pathogen. In the examination of seed-borne microorganisms of soybean (Glvcine max (L.) Merrill cultivar Palmet to, SJ4 and SJ5 collected from Malaysia and Thailand, nine genera comprising of 13 species of fungsi were found to be associated with the seeds. Among these fungi, Colltotrichum truncatum incidence was recorded in the range of 2.5-6.5%. The blotter method proved more suitable for detecting C. truncatum than agar plate method.